The Effect Of Consumer Relations And Interactive Marketing On Customer Loyalty With Customer Satisfaction As A Mediating Variable (Case Study on Es Teh Indonesia Madiun City): Integrating Government, Community, and Marketing Strategies - Indra Ayu Fatmala; Zalza Dela Novita (Cita Konsultindo Research Center, 2024)
The Influence of Consumer Relations and Interactive Marketing towards Consumer Loyalty with Consumer Satisfaction as a Mediating Variable (Case Study of Es Teh Indonesia in Madiun City).This thesis was based on several things which should be considered to create customer satisfaction and loyalty. One of the things which could create consumer satisfaction and loyalty is building good relationships and interactive marketing with consumers. The aim of this research was to determine the effect of consumer relations, interactive marketing towards consumer loyalty, consumer satisfaction as a mediating variable for Es Teh Indonesia consumers in Madiun City. The research sample was 384 respondents. The research method used was a quantitative approach using purposive sampling techniques and using the SPSS version 23 program. The results of this research are that consumer relations do not have a significant effect towards consumer loyalty. Interactive Marketing has a significant effect towards Consumer Loyalty. Consumer Relations, Interactive Marketing has a significant effect towards Consumer Satisfaction. Consumer Satisfaction has a significant effect towards Consumer Loyalty. Consumer Relations, Interactive Marketing has a significant effect towards Consumer Loyalty with Consumer Satisfaction as a mediating variable.